A Flexible Nonlinear Inference to Okun’s Law for Turkish Economy in the Last Decade - Arabaci, Özer; Arabaci, Rabihan Yuksel (Panoeconomicus, 2018)
The study applies the flexible nonlinear inference approach of James D. Hamilton (2001) to investigate the relationship between cyclical components of unemployment and output in the Turkish economy where the unemployment rate remains at double digits despite the relatively stable economic environment over the last decade. The paper shows that economic expansion and contraction terms have an asymmetric effect on cyclical unemployment in Turkey. Moreover, the study identifies a specific range for the output gap level at which jobless growth pattern occurs in the Turkish economy. According to our findings, contrary to standard literature, cyclical component of unemployment does not decrease even though cyclical component of output is positive and increases in the middle stages of the upswing phase of the economy. This result may also indicate that the employers are reluctant to extend employment and alter into informalization for reasons such as over-valued domestic currency, surplus labour force and/or any rigid regulatory frameworks in the middle stages of the expansion phase of the economy. However, they become eager to expand employment and renounce informalization only after a certain rate of economic growth is achieved. Keywords: Okun’s Law, Flexible nonlinear inference, Jobless growth, Turkey. JEL: C50, E24. Fleksibilni nelinearni zaključak Okunovog zakona o Turskoj ekonomiji u poslednjoj deceniji Istraživanje primenjuje fleksibilni pristup nelinearnog zaključivanja Jamesa D. Hamiltona (2001) za istraživanje odnosa između cikličnih komponenti nezaposlenosti i proizvodnje u Turskoj ekonomiji gde stopa nezaposlenosti ostaje dvostruka cifra uprkos relativno stabilnom ekonomskom okruženju tokom poslednje decenije. Rad pokazuje da uslovi ekonomske ekspanzije i kontrakcije imaju asimetrični efekat na cikličnu nezaposlenost u Turskoj. Štaviše, istraživanje identifikuje specifičan opseg za proizvodni jaz na kojem se odvija obrazac rasta nezaposlenosti u Turskoj ekonomiji. Prema našim nalazima, suprotno standardnoj literaturi, ciklična komponenta nezaposlenosti se ne smanjuje, iako je ciklična komponenta proizvodnje pozitivna i povećava se u srednjim fazama ekspanzije privrede. Ovaj rezultat takođe može ukazivati na to da poslodavci nisu spremni da zapošljavaju i prihvate neformalizam iz razloga kao što su precenjena domaća valuta, višak radne snage i/ili bilo kakvi rigidni regulatorni okviri u srednjoj fazi ekspanzije ekonomije. Međutim, oni žele da zapošljavaju i odustanu od formalizma tek nakon postizanja određene stope ekonomskog rasta. Ključne reči: Okunov zakon, fleksibilno nelinearno zaključivanje, rast nezaposlenosti, Turska.